Identifying Student Interests in the Vocational Field Using the Certainty Factor Method - Puspita, Poppy; Ramadani, Ramadani; Sitompul, Juliana Naftali (International Journal of Informatics, Economics, Management and Science, 2023)
SMK Negeri 1 Kota Binjai is a vocational high school that has several competency skills majors. This school has an interest in applicants who are quite interested every year, the number of applicants in admitting new students every year continues to increase from year to year. Vocational education is an educational model that focuses on individual skills, skills, work habits, and appreciation of the jobs needed by people in the business/industry world. Lack of information about talent interests and career paths or vocational education greatly affects students in making choices regarding majors. Many students who choose majors are not interested in their talents and other reasons. This can make students wrong in taking a major which causes inadequate competence of students in completing their education and will certainly affect the future of these students. expert system which is a computer program, which is able to store knowledge and rules like an expert. With the existence of an expert system, each student is able to identify and find out what areas of expertise he is interested in. The Certainty Factor method is a method for proving whether a fact is certain or uncertain in the form of a metric which is usually used in expert systems. From the results of trials conducted by the expert system to identify students' interest in the vocational field using the Certainty Factor method, the highest score is majors Online Business and Marketing with a confidence value of 89.67%.